To solve the equation \((x + 36)^2 - 38 = 251\), we can first rearrange it.
-
Add 38 to both sides: \[ (x + 36)^2 = 251 + 38 \] \[ (x + 36)^2 = 289 \]
-
Now, take the square root of both sides: \[ x + 36 = \pm \sqrt{289} \] \[ x + 36 = \pm 17 \]
-
Now solve for \(x\):
-
For the positive case: \[ x + 36 = 17 \] \[ x = 17 - 36 \] \[ x = -19 \]
-
For the negative case: \[ x + 36 = -17 \] \[ x = -17 - 36 \] \[ x = -53 \]
-
Thus, the solutions to the equation are: \[ {-19, -53} \]
So the correct answer is \({−19,−53}\).